Single molecule force spectroscopy studies of DNA denaturation by T4 gene 32 protein. Issue 2 (2004) - Williams Williams, Mark C. Mark C.; Pant Pant, Kiran Kiran; Rouzina Rouzina, Ioulia Ioulia; Karpel Karpel, Richard L. Richard L.
Abstract : Single molecule force spectroscopy is an emerging technique that can be used to measure the biophysical properties of single macromolecules such as nucleic acids and proteins. In particular, single DNA molecule stretching experiments are used to measure the elastic properties of these molecules and to induce structural transitions. We have demonstrated that double‒stranded DNA molecules undergo a force‒induced melting transition at high forces. Force–extension measurements of single DNA molecules using optical tweezers allow us to measure the stability of DNA under a variety of solution conditions and in the presence of DNA binding proteins. Here we review the evidence of DNA melting in these experiments and discuss the example of DNA force‒induced melting in the presence of the single‒stranded DNA binding protein T4 gene 32. We show that this force spectroscopy technique is a useful probe of DNA–protein interactions, which allows us to obtain binding rates and binding free energies for these interactions.